Urban Times: Temporal Topographies and Non-scalable Cities†. Issue 3 (27th May 2017) - Nielsen, Morten
ABSTRACT: Whereas 'urban' is usually considered as designating a particular spatial environment composed by the agglomeration of human and non-human elements, the notion of 'time' suggests a processual dynamic of rhythms and velocities. However, if we take as a speculative premise that the oxymoronic idea of 'urban times' does capture a particular experiential modality, the analytical challenge is obviously to explore what its status might be and how it can be subjected to anthropological examination. In this article, I introduce temporal topographies as an analytical heuristics for examining the oxymoronic constellation 'urban times'. Taken to constitute partially coordinated complexes of spatio-temporal rhythms, temporal topographies assert themselves as theories that cities make of themselves without being able to totalize the spatio-temporal landscape. It is, however, precisely because they are constantly on the verge of breaking down that temporal topographies give to urban life a particular and awkward potency.